"It's not easy feeling like me": emotion regulation and self-integration in adolescent self-harm - Phillips, Katherine Freya Vivienn (The University of Edinburgh, 2006)
Previous studies have found that the reduction of negative emotions, and the creation of sensation to counteract loss of sense of self, are the most frequently reported motivations for self-harm. The current study aimed to investigate the influence of emotion regulation and self-integration on self-harm in a sample of adolescents. Analyses found that adolescents who self-harm, from both a non-clinical and a clinical sample, used dysfunctional emotion regulation strategies more frequently, and functional strategies less frequently, than adolescents who had not self-harmed. Significant correlations between emotion regulation and level of self-harm were also found. Analyses also found that adolescents who self-harm had a lower level of self-integration than adolescents who had not self-harmed. Significant correlations between level of self-integration and level of self-harm were also found. Emotion regulation and self-integration predicted self-harm in regression analyses, as did depression. A path analysis supported the hypothesis that attachment was a key developmental factor in emotion regulation, which in turn predicted self-harm directly, as well as indirectly via level of self-integration and depression. The motivation to self-harm, both to create feelings and to avoid feelings, appears to reflect the use of dysfunctional emotion regulation strategies and the sense of poor self-integration.